Parables of our time: faith in contemporary fiction. Issue 1 (January 2023) - James, Graham
An influential former Bishop of Norwich explores the work of four novelists – Salley Vickers, Susan Hill, Rachel Joyce and Anne Tyler – as 'parables of our time'.